Impact of historical contamination on meiofaunal assemblages: The case study of the Bagnoli-Coroglio Bay (southern Tyrrhenian Sea). (April 2020) - Gambi, C.; Dell'Anno, A.; Corinaldesi, C.; Lo Martire, M.; Musco, L.; Da Ros, Z.; Armiento, G.; Danovaro, R.
Abstract: The effects of contaminants on marine organisms have been documented since decades, but the long-term responses and recovery rates of benthic communities to mixtures of contaminants, several years after the cessation of industrial activities, need to be further investigated. Bagnoli-Coroglio Bay (Gulf of Naples, Tyrrhenian Sea) is a typical example of historically contaminated coastal area due to industrial activities stopped at the beginning of nineties. In the present study we carried out a fine spatial scale analysis of the distribution of meiofaunal (and nematodes) assemblages along five bathymetric transects located at increasing distance from the historical source of contamination in relation with the polycyclic aromatic hydrocarbon and heavy metal concentrations present in the sediment. Meiofaunal abundance and biomass changed widely along transects but independent from the distance from the source of contamination. Even when the contamination levels were expected to induce significant detrimental biological consequences, meiofaunal abundance and biomass were similar to those reported in unpolluted benthic coastal areas worldwide. Conversely, biodiversity in terms of meiofaunal taxa richness was generally low (range: 5–8 taxa in 12 of the overall 15 stations investigated). This was explained by the lack of sensitive groups such as ostracods, gastrotrichs and tardigrades commonly encountered in benthic coastal ecosystems, thus reflecting an overall poor/moderate environmental quality of the investigated area. Nematode (structural and functional) diversity was also low, particularly at stations characterized by higher contamination levels. At the same time, nematode species composition did not change significantly among stations suggesting a widespread effect of contaminants able to reduce the variability (i.e., turnover diversity) within the assemblages of the whole study area. Overall, our results indicate that even decades after the cessation of contaminant emissions, benthic biodiversity was affected in terms of both meiofaunal taxa and nematode species. These findings strongly reinforce the call for reducing sources of chronic pollution in marine ecosystems and provide new insights for a better understanding of the ecological recovery of historically contaminated marine environments. Highlights: The effects of historical contamination is evident on benthic diversity. Meiofaunal abundance and biomass are less affected by the contamination. The highly contaminated sediments are mostly characterized by the tolerant nematode species. Investigating historically contamination is crucial for the assessment of the ecological recovery.